2018
DOI: 10.1063/1.5017889
|View full text |Cite
|
Sign up to set email alerts
|

Observations of non-linear plasmon damping in dense plasmas

Abstract: We present simulations using finite-temperature density-functional-theory molecular-dynamics to calculate dynamic dielectric properties in warm dense aluminum. The comparison between exchange-correlation functionals in the Perdew, Burke, Ernzerhof approximation, Strongly Constrained and Appropriately Normed Semilocal Density Functional, and Heyd, Scuseria, Ernzerhof (HSE) approximation indicates evident differences in the electron transition energies, dc conductivity, and Lorenz number. The HSE calculations sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 88 publications
6
39
1
Order By: Relevance
“…The new table is compared with that of experiments in the liquid regime in Figure . These data have recently been confirmed by Leitner et al Also shown are DFT‐MD results by Witte et al The new table agrees well with the PBE calculations, as expected, since it was constructed to match our own PBE calculations in this regime (but not these exact points). The table and the PBE results overestimate the data.…”
Section: Construction Of Tablesupporting
confidence: 84%
See 1 more Smart Citation
“…The new table is compared with that of experiments in the liquid regime in Figure . These data have recently been confirmed by Leitner et al Also shown are DFT‐MD results by Witte et al The new table agrees well with the PBE calculations, as expected, since it was constructed to match our own PBE calculations in this regime (but not these exact points). The table and the PBE results overestimate the data.…”
Section: Construction Of Tablesupporting
confidence: 84%
“…The table and the PBE results overestimate the data. HSE calculations by the same authors demonstrate sensitivity to the exchange and correlation potential in this regime.…”
Section: Construction Of Tablementioning
confidence: 74%
“…Assuming an accuracy better than ±10% is required for the DC conductivity, it is clear that the classical log Λ results cover only a limited region of phase space, and the more accurate quantum approach must be used elsewhere. As a final example to highlight this result, in figure 9 these models are compared to recent Kubo-Greenwood, DFT-MD simulation results [33] for solid density aluminum in the relatively low temperature regime. There are two sets of DFT-MD results corresponding to two different exchange and correlation potentials (PBE [34] and HSE [35]).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, quantum molecular dynamics (QMD) simulations can be used which treat the nuclei classically and the electrons quantum mechanically within finite‐temperature density‐functional theory (DFT). Although they have proven to be a versatile tool for calculating the equation of state, optical, and transport properties of WHDM, QMD simulations are computationally demanding so that simpler methods are still appropriate.…”
Section: Introductionmentioning
confidence: 99%